2011
DOI: 10.1589/jpts.23.595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Therapy on the Body Composition and Blood Components of Obese Men

Abstract: Abstract.[Purpose] The purpose of this study was to examine the effects of an eight-week exercise program on body composition, blood lipids, and hormone levels of 16 obese adult males. [Subjects and Methods] After an experimental group (n=8) and a control group (n=8) were organized, subject were examined: then, the experimental group performed endurance exercises for 8 weeks. At the end of the eight weeks, the two groups were examined again for weight, % body fat, and body fat mass via a bioelectrical impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…The present study also found an inverse correlation between BMI and some physical activities. This agrees with Han et al 24 ) who reported that physical exercises reduces %body fat, body fat mass and blood lipids. Also, the results of various researches show that the IQ of children is negatively linked with childhood obesity 25 ) .…”
Section: Discussionsupporting
confidence: 93%
“…The present study also found an inverse correlation between BMI and some physical activities. This agrees with Han et al 24 ) who reported that physical exercises reduces %body fat, body fat mass and blood lipids. Also, the results of various researches show that the IQ of children is negatively linked with childhood obesity 25 ) .…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that young adults with a sedentary lifestyle were compliance to the 8-week resistance exercise program. However, further studies are needed to study the long-term effects of resistance exercise on cardiovascular outcomes and its effects in other patient settings 11 , 12 , 13 , 14 , 15 , 16 , 17 ) . The other advantage of this study is that it was a randomized control trial.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exercise is recommended as a program to resolve obesity. In their research, Saris et al 16 ) observed that exercise for 45 to 60 minutes was needed, while Lee 17 ) asserted that exercise of moderate intensity at least five days a week was effective. In contrast to previous research, however, the intervention in the present study was effective for decreasing body fat only; it is considered that this was because the intervention period was relatively shorter than those of previous studies.…”
Section: Discussionmentioning
confidence: 99%